Marketing Strategy During The Covid-19 Pandemic and Its Influence on The Purchase Decision of Subsidized Housing In Maros Regency: Mixed-Method Approach - Sri Rahmi; Heriyanti Mustafa (Program Pascasarjana STIE Amkop Makassar, 2022)
Abstrak This study aims to analyze the marketing strategy of subsidized housing during the covid-19 pandemic and its effect on purchasing decisions. The research phase begins with a qualitative approach to formulating hypotheses through a mixed-method approach with sequential exploratory design. In this stage, data we collect data from interviews with subsidized housing developers in Maros Regency, South Sulawesi. The final result of the qualitative stage is to develop a hypothesis that service quality (servqual) and word of mouth (wom) affect the purchase decision. Furthermore, we collected data from 132 low-income communities (MBR) and bought subsidized houses in Maros Regency with a quantitative approach. With the analysis of Structural Equation Modeling (SEM) using AMOS 23, the results of this study indicate that servqual has a positive and significant effect on WOM and purchase decisions. Likewise, the influence of WOM on purchase decisions is positive and significant. The results of the analysis also show that WOM is a variable that is able to mediate the relationship between servqual and purchase decisions. Kata Kunci: service quality, word of mouth, purchase decision, subsidized housing